Short high‐fat diet interferes with the physiological maturation of the late adolescent mouse heart - Heidi Hynynen; Maija Mutikainen; Nikolay Naumenko; Anastasia Shakirzyanova; Tomi Tuomainen; Pasi Tavi (Physiological Reports, 2020)
Abstract Dietary fats are essential for cardiac function. The metabolites of fats known as fatty acids provide most of the energy for cardiac tissue, serve as building blocks for membranes and regulate important signaling cascades. Despite their importance, excess fat intake can cause cardiac dysfunction. The detrimental effects of high‐fat diet (HFD) on cardiac health are widely investigated in long‐term studies but the short‐term effects of fats have not been thoroughly studied. To elucidate the near‐term effects of a HFD on the growth and maturation of late adolescent heart we subjected 11‐week‐old mice to an 8‐week long HFD (42% of calories from fat, 42% from carbohydrate, n = 8) or chow diet (12% of calories from fat, 66% from carbohydrate, n = 7) and assessed their effects on the heart in vivo and in vitro. Our results showed that excessive fat feeding interferes with normal maturation of the heart indicated by the lack of increase in dimensions, volume, and stroke volume of the left ventricles of mice on high fat diet that were evident in mice on chow diet. In addition, differences in regional strain during the contraction cycle between mice on HFD and chow diet were seen. These changes were associated with reduced activity of the growth promoting PI3K‐Akt1 signaling cascade and moderate changes in glucose metabolism without changes in calcium signaling. This study suggests that even a short period of HFD during late adolescence hinders cardiac maturation and causes physiological changes that may have an impact on the cardiac health in adulthood.